Leveraging ELAN Software for Analyzing Storytelling Gestures in Students at SMAN 1 Semaka - Siti Badriyah; Susanto, Susanto; Yanuarius Yanu Dharmawan (Cita konsultindo, 2024)
This study investigates the use of nonverbal communication (NVC), namely gestures, in the narrative exercises of students at SMAN 1 Semaka. The objective is to determine and classify the precise types and frequencies of gestures used. The use of ELAN software allows for a thorough study, which shows that specific gestures, such as Open Hands (OP) and Head Tilting (HT), are commonly employed and have a substantial impact on improving the delivery of a narrative. On the other hand, gestures such as Hands on Hips (HH) and Hand on Cheek (HCH) were not frequently seen, indicating that their significance may vary depending on the situation and the individual's way of expressing a tale. This study highlights the significance of incorporating Nonviolent Communication (NVC) into educational methods in order to enhance students' proficiency in communication and storytelling. This study enhances our overall comprehension of nonverbal communication in educational environments and emphasises the usefulness of technological tools such as ELAN in furthering educational research.